2012
DOI: 10.5829/idosi.ijee.2012.03.05.06
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Precipitation of Ammonia and Phosphate from Nam Son Landfill Leachate, Hanoi

Abstract: Abstract:Leachate from municipal landfills of the city is often contaminated heavily, especially for parameters such as organic components, heavy metals, microorganisms. However, leachate also contains amounts of valuable nutrients (e.g. N, P, K) which can be used for agriculture as fertilizers. Precipitated of N and P in the form of struvite (MgNH 4 PO 4 .6H 2 O) might be applied as a technique for removal a huge amount of N as well as P in wastewater. This study investigated the recovery ability of N, P in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…The average concentration of COD before treatment was calculated 5163.6 and reduced to 1715.2 mg/L after treatment which showed a reduction of 66.8% of COD. Similar outcome has been reported earlier 5,13 which were 61 and 63.11% respectively. In a hydroponic experiments, investigated 24,25 showed that vetiver grass has the ability to survive in leachate with COD of 750 mg/L to 2600 mg/L and this research showed that vetiver grass could still survive in the 100% leachate strength in which the COD value was 6930, which is a high COD value.…”
Section: Dry Weight Of Shoots and Roots After Treatmentssupporting
confidence: 92%
See 1 more Smart Citation
“…The average concentration of COD before treatment was calculated 5163.6 and reduced to 1715.2 mg/L after treatment which showed a reduction of 66.8% of COD. Similar outcome has been reported earlier 5,13 which were 61 and 63.11% respectively. In a hydroponic experiments, investigated 24,25 showed that vetiver grass has the ability to survive in leachate with COD of 750 mg/L to 2600 mg/L and this research showed that vetiver grass could still survive in the 100% leachate strength in which the COD value was 6930, which is a high COD value.…”
Section: Dry Weight Of Shoots and Roots After Treatmentssupporting
confidence: 92%
“…If the leachate goes unattended by percolation into subsoil layers, it can deteriorate the underlying soil and groundwater 4 . The quantity and quality of leachate depends upon the source of water entering into the dumpsite 5 .…”
mentioning
confidence: 99%
“…This landfill with area of 83.5 hectares has started mechanized operation in 1999 and expanded to 112 hectares in 2015. Currently, Nam Son landfill receives about 4300 to 4500 tons of waste per day and approximately 2000 m 3 leachate, yet only 1500 m 3 leachate is treated daily [5].…”
Section: Landfill Site Description and Leachate Characteristicsmentioning
confidence: 99%
“…Selain itu struvite menjadi sumber N, Mg 2+ , dan P yang sangat efektif untuk tanaman dan dapat digunakan sebagai pupuk slow release tanpa merusak akar tanaman [5;6]. Presipitasi struvite dipengaruhi oleh beberapa faktor, diantaranya pH, komposisi kimia air limbah (derajat kejenuhan terhadap magnesium, amonium dan fosfat; kehadiran ion lainnya; kekuatan ion) dan suhu larutan [7]. Faktor yang paling berpengaruh pada presipitasi struvite adalah rasio molar Mg 2+ : NH4 + :PO4 3dan pH [8] Presipitat hasil presipitasi optimum akan dianalisis morfologi dan strukturnya menggunakan SEM-EDX.…”
Section: Pendahuluanunclassified